2019
DOI: 10.1155/2019/3687873
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Intensity of Soil-Transmitted Helminth Infection among Rural Community of Southwest Ethiopia: A Community-Based Study

Abstract: Background. Helminths are significant contributors to global health problems. Subgroup soil-transmitted helminths are among the listed neglected tropical diseases. The rural inhabitants often suffer from heavy infection, particularly children and pregnant women. Objective. The study aimed at determining the magnitude and intensity of soil-transmitted helminth infection and associated risk factors in the study area where the prevalence and intensity of the infection are yet unknown at the community level. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
22
10
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 22 publications
11
22
10
2
Order By: Relevance
“…The overall prevalence of STH infections observed in this study is comparable with studies conducted in another parts of Ethiopia (Butajira and Wonji) and West China [2628], but slightly lower than the prevalence reported in Dembiya, northwest Ethiopia [21]. In addition, the prevalence in our study is significantly lower than the findings of other studies conducted in another part of Nigeria, Cameroon, Ecuador, Uganda, Kenya and Honduras [2936]. These differences observed from our study could be due to variation in socio-cultural, social determinants, behavioral characteristics and implementation of prevention and control measures.…”
Section: Discussionsupporting
confidence: 79%
“…The overall prevalence of STH infections observed in this study is comparable with studies conducted in another parts of Ethiopia (Butajira and Wonji) and West China [2628], but slightly lower than the prevalence reported in Dembiya, northwest Ethiopia [21]. In addition, the prevalence in our study is significantly lower than the findings of other studies conducted in another part of Nigeria, Cameroon, Ecuador, Uganda, Kenya and Honduras [2936]. These differences observed from our study could be due to variation in socio-cultural, social determinants, behavioral characteristics and implementation of prevention and control measures.…”
Section: Discussionsupporting
confidence: 79%
“…On the contrary, the STH prevalence in our study is slightly lower than the prevalence reported in Dembiya, northwest Ethiopia [19]. In addition, the prevalence in our study is significantly lower than the findings of other studies conducted in another part of Ethiopia and in Nigeria, Cameroon, Ecuador, Uganda, Kenya and Honduras [28][29][30][31][32][33][34][35]. These differences observed from our study could be due to variation in socio-cultural, social determinants, behavioral characteristics and implementation of prevention and control measures.…”
Section: Plos Onecontrasting
confidence: 80%
“…The occupation level was statistically significant to STH and S. mansoni infection, and this was also observed by Naish et al [ 30 ]. This study noted that eating unwashed fruits and vegetables was attributed to STH infection, which agrees with findings from previous studies [ 27 , 31 ]. The observation made can be explained by what was observed by Bekele et al [ 32 ] and Tefera et al [ 33 ] in their study on parasitic contamination of raw vegetables and fruits, where they concluded that the fruits and vegetables were contaminated with STH.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of T. trichiura was also low, which is different from the prevalence observed in South Nyanza [ 20 ], and this agrees with another study by Loukouri et al [ 18 ] in Eastern Cote d'Ivoire. Multiple infections between A. lumbricoides and hookworm were observed in this study which agrees with other studies [ 24 27 ] in which they observed multiple infections that are polyparasitism, coinfection of two STH species, and coinfection with three soil-transmitted species. Shitaho Primary School accounted for the highest prevalence of STH, and this is in tandem with Ngonjo et al [ 7 ].…”
Section: Discussionsupporting
confidence: 92%